Recurrent coronary circulation disturbances in acute myocardial infarction - V. A. Lusov; A. Yu. Lebedeva; E. V. Petrova; N. A. Volov; I. G. Gordeev; L. L. Klykov (Российский кардиологический журнал)
The review is devoted to systemic thrombolysis in patients with acute myocardial infarction, as one of the most accessible reperfusion methods. The link between post-thrombolysis infarct-related artery status and future coronary heart disease progression is emphasized. Post-thrombolysis treatment strategy is discussed. Aggressive tactics in patients with recurrent coronary circulation disturbances improves clinical outcomes.